2009
DOI: 10.1172/jci38662
|View full text |Cite|
|
Sign up to set email alerts
|

Normal mouse intestinal mucus release requires cystic fibrosis transmembrane regulator–dependent bicarbonate secretion

Abstract: The mechanisms underlying mucus-associated pathologies in cystic fibrosis (CF) remain obscure. However, recent studies indicate that CF transmembrane conductance regulator (CFTR) is required for bicarbonate (HCO 3 -) transport and that HCO 3 -is critical for normal mucus formation. We therefore investigated the role of HCO 3 -in mucus secretion using mouse small intestine segments ex vivo. Basal rates of mucus release in the presence or absence of HCO 3 -were similar. However, in the absence of HCO 3 -, mucus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
242
3
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 261 publications
(260 citation statements)
references
References 59 publications
(84 reference statements)
12
242
3
3
Order By: Relevance
“…The exact physiological significance of the PTH-stimulated HCO 3 Ϫ secretion in vivo remains elusive, but it might contribute to intestinal mucous and fluid secretion, optimization of extracellular pH in the brush border microclimate, and/or maintenance of the intracellular pH and volume (13,22). Our preliminary study in the in situ ligated loops of various rat intestinal segments revealed a significant dilution of sodium ferrocyanide, a nonabsorbable marker of water transport, only in the ileum within 20 min after a single intravenous PTH administration (S. Laohapitakworn and N. Charoenphandhu, unpublished observations), suggesting that PTH induced fluid secretion in rat ileum.…”
Section: Discussionmentioning
confidence: 99%
“…The exact physiological significance of the PTH-stimulated HCO 3 Ϫ secretion in vivo remains elusive, but it might contribute to intestinal mucous and fluid secretion, optimization of extracellular pH in the brush border microclimate, and/or maintenance of the intracellular pH and volume (13,22). Our preliminary study in the in situ ligated loops of various rat intestinal segments revealed a significant dilution of sodium ferrocyanide, a nonabsorbable marker of water transport, only in the ileum within 20 min after a single intravenous PTH administration (S. Laohapitakworn and N. Charoenphandhu, unpublished observations), suggesting that PTH induced fluid secretion in rat ileum.…”
Section: Discussionmentioning
confidence: 99%
“…Whether the abnormalities in CF mucus result from reduced liquid volume, decreased HCO 3 − concentration, abnormally acidic pH, or some combination of these is uncertain (21). A reduced HCO 3 − concentration was reported to contribute to intestinal mucin abnormalities in CF mice (36)(37)(38). In CF pigs, a decreased pH, rather than a decreased HCO 3 − concentration, increased airway surface liquid viscosity (29).…”
Section: Muc5b Forms Mucus Strands and Muc5ac Forms Mucus Threads Andmentioning
confidence: 99%
“…We speculate that the role of CHE cells is to liquefy lumen content and thus assist in mucus clearance. The proximal jejunum, where CHE cells are most abundant, possesses a particularly low luminal pH that can promote accumulation of firm adherent mucus on epithelial surfaces and intervillus spaces (18,24,28). Indeed, CFTR abundance in CHE cells increases as the cells migrate toward the villus tip, suggesting that the most robust secretion emanates from CHE cells in the villus region.…”
Section: G462mentioning
confidence: 99%